G151(P) Impact of a Training Programme on Non-Medical Health Workers Confidence in Managing Common Neonatal Problems in Sierra Leone. (4th June 2013) - Morrissey, B; Kenny, T; Williams, S; Waddington, D
Abstract : Background and Aims: Sierra Leone has one of the highest infant mortality rates in the world, with 113 out of every 1000 live births dying in their first year of life. Many of these deaths occur in the first month of life from birth asphyxia, complications of low birth weight and prematurity and neonatal sepsis. Sierra Leone has a critical shortage of health workers, especially those with skills in neonatal care. We aimed to develop and evaluate the impact of a two-day training programme designed to give non-medical health workers the knowledge and skills required to provide essential neonatal care to sick and low birth weight neonates. Methods: Twenty-six health workers competed the training programme which was run in the central government hospitals in two neighbouring districts in Sierra Leone. The programme included interactive lectures, practical demonstrations and small-group facilitated sessions, which gave participants the opportunity to practise their newly acquired skills in simulated clinical scenarios. Simplified neonatal treatment guidelines, based on World Health Organisation best practise, were developed and given to each participant to be used during the workshop and as an ongoing reference. Participants were asked to complete a confidence questionnaire before and after the programme: pre and post course confidence scores were analysed. Results: Participants included 18 nursing staff, 5 community health officers and 3 nursing aides. In one district a neonatal unit had just opened in the central government hospital, and in the other district a neonatal unit was planned with the opening of a new Africa Development Bank funded maternity unit. Health workers showed a significant (p < 0.001) increase in their confidence in managing common neontal problems as illustrated in Table 1 . Conclusion: A two-day training programme, coupled with the provision of clinical guidelines, significantly increased the confidence of non-medical health workers in managing the most commonly encountered neonatal problems in Sierra Leone. This demonstrates the potential of the task-shifting approach to expand access to essential neonatal services in similar resource-constrained settings. Further work is required to assess whether changes to practise are sustained, and to evaluate their effects on neonatal outcomes.